Sacred Sounds in Transit: The Transformation of Indonesian Ritual Music as a Creative Economy Commodities - Citra Aryandari (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2025)
This critical ethnographic study examines the Indonesian ritual music transformation into creative economy commodities, revealing complex negotiations between cultural preservation and market logic. Its primary contribution is a multi-actor governance model that reveals how Indonesian ritual music is strategically managed within a competitive ecosystem of power. Through multi-sited fieldwork, this study examines how Indonesian ritual music is reconfigured for tourism, negotiating between spiritual authenticity and commercial viability. Employing a mixed-method approach that combines critical reanalysis of existing ethnographic documentation with targeted primary fieldwork, the study traces power dynamics underlying commodification processes through multi-temporal perspectives. The research engaged a diverse range of informants, including traditional practitioners, PINKAN officials, government representatives, and multi-general artist to ground this analysis. Intensive participant observation during UNESCO recognition processes was supplemented by validation fieldwork across all three sites to capture contemporary transformations. Findings reveal that ritual music's market transit generates stratified outcomes where local communities, state agencies, and global markets compete for definitional authority over cultural meaning. While creative economy initiatives provide economic incentives for cultural transmission, they simultaneously restructure traditional authority, privileging market-oriented aesthetics over cosmological meanings. Traditional leaders function as